2005
DOI: 10.1007/s00454-004-1156-9
|View full text |Cite
|
Sign up to set email alerts
|

Almost Periodic Measures and Long-Range Order in Meyer Sets

Abstract: The main result of this paper is that the diffraction pattern of any Meyer set with a well-defined autocorrelation has a relatively dense set of Bragg peaks. In the second part of the paper we provide a necessary and sufficient condition for a positive pure point measure to have a continuous Fourier transform. In particular, one can get a necessary and sufficient condition for a point set to have no Bragg peaks in its diffraction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
106
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(111 citation statements)
references
References 28 publications
5
106
0
Order By: Relevance
“…Amusingly enough, this property was shown in 2005 to be one of the main ingredients in the Strungaru theorem that states that a Delaunay distribution of atoms has a sharp diffractive component in its Fourier spectrum if the pair interatomic vectors form a uniformly discrete set. [9] The Blech model has been the starting point of an enormous body of work on random tilings, especially in the United States, mainly by theoretical physicists.…”
Section: A the Blech Modelmentioning
confidence: 99%
“…Amusingly enough, this property was shown in 2005 to be one of the main ingredients in the Strungaru theorem that states that a Delaunay distribution of atoms has a sharp diffractive component in its Fourier spectrum if the pair interatomic vectors form a uniformly discrete set. [9] The Blech model has been the starting point of an enormous body of work on random tilings, especially in the United States, mainly by theoretical physicists.…”
Section: A the Blech Modelmentioning
confidence: 99%
“…On the other hand, the function giving the intensity per diffracting site of Z β is defined as [10] it can be shown that the values of (4.21) at the points of the pure-point spectrum of µ are the intensities of the Bragg peaks; see for instance Definition 3.1 in Strungaru [39]. This statement originates in the so-called…”
Section: Diffraction Spectrum Of a Set Of Weighted Beta-integersmentioning
confidence: 99%
“…Under such assumptions, the autocorrelation is even the sum of two pure point measures (Proposition 3.3 in [39] show a need for introducing new theories to describe the structure of this spectrum. By Section 3 the elements in Z β are in one-to-one correspondence with elements of (−β, β) (Proposition 3.1) by the * -operation.…”
Section: Annales De L'institut Fouriermentioning
confidence: 99%
“…A particularly relevant class of point sets in the theory of aperiodic order are Meyer sets, which are relatively dense sets Λ such that Λ − Λ is uniformly discrete. Such sets always have a diffraction measure with a non-trivial pure point part, with a relatively dense supporting set [59,2], despite the fact that Meyer sets can have entropy 2 . If modified by a family of random measures according to Theorem 2, the resulting diffraction still shows the original diffraction with its non-trivial pure point component, modulated by the function E Q (Ω)…”
Section: Theorem 2 Letmentioning
confidence: 99%